Digestive enzymes during different life stages in three species of carps - Srikar, L N; Phadate, S V; Reddy, G Vidya Sagar (Indian Journal of Fisheries, 2011)
Kawai and Ikeda (1973) suggested thathatching enzymes consist of severalhydrolases, including proteolytic and lipolyticenzymes. In carnivorous fish like salmon andblack sea bream peptic activity, and instomachless fish like common carp trypticactivity have a role in hatching (Kawai andIkeda 1973).